Assessment of hospital waste management in a major city of Pakistan. (2017) - Ali, Mustafa; Wang, Wenping; Chaudhry, Nawaz
Proper management of healthcare waste is a critical concern in many resource constrained countries of the world. Pakistan is the sixth most populous country in the world with one of the highest urbanisation and population growth rates in South Asia. Data and analyses regarding hospital waste management practices in Pakistan are scarce in scientific literature. This study was meant to determine waste management practices at the largest hospital in a major city of Pakistan. The hospital was thoroughly analysed for a week to quantify its wastes by category using a digital balance. Medical waste generation at the hospital came out as 2.63 Kg/patient-day of which 6.8% consisted of sharps and the remaining consisted of hazardous infectious items. Gynaecology and paediatrics wards had the largest and the smallest waste generation rates respectively. More than 1.06 Tonne of general waste was also generated at the hospital. Waste segregation, storage, transportation and disposal practices at the hospital had serious shortcomings.